Pengaruh Penghargaan Finansial, Pertimbangan Pasar Kerja, dan Lingkungan Kerja Terhadap Minat Pemilihan Karir Mahasiswa Akuntansi Sebagai Akuntan Publik (Studi Empiris pada Mahasiswa Akuntansi di Politeknik Negeri Lampung) - Natasya Febrina Putri; Evi Yuniarti; M. Muhayin A. Sidik (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research was conducted to determine the influence of financial rewards, job market considerations, and the work environment on accounting students' interest in choosing a career as a public accountant. Case study accounting students at the Lampung State Polytechnic. This research uses a quantitative approach method obtained from primary data by distributing questionnaires to respondents. Sampling in this study used probability sampling with a simple random sampling technique and a sample of 90 respondents was obtained using the Slovin formula. The data analysis technique used is Structural Equation Modeling (SEM) using smart-PLS 3.2.9 software. The results of this research show that financial rewards and job market considerations do not influence accounting students' interest in choosing a career as a public accountant. Meanwhile, the work environment has a significant influence on accounting students' interest in choosing a career as a public accountant